1997
DOI: 10.3168/jds.s0022-0302(97)76147-2
|View full text |Cite
|
Sign up to set email alerts
|

Immune Recruitment and Bactericidal Activity of Neutrophils in Milk of Cows Vaccinated with Staphylococcal α-Toxin

Abstract: The ability of Staphylococcus aureus alpha-toxin to recruit neutrophils in the milk of vaccinated cows and the bactericidal efficiency of these neutrophils were evaluated. Six lactating Holstein cows that were free of intramammary infection received systemic immunization by subcutaneous injection of Freund's incomplete adjuvant with alpha-toxin (n = 2), alpha-toxin mixed with type 5 capsular polysaccharide (n = 2), or a conjugate of these two antigens (n = 2). Controls (n = 4) and vaccinated cows (n = 6) recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…This is precisely the density of blood-derived PMN necessary to exert optimal bactericidal (Staph. aureus) activity in milk, as reported by Herbelin et al (1997), but higher than 6 × 10 5 cells/ mL, as reported by Postle et al (1978). It is also close to the SCC value (1,151,000 cells/mL) reported in the meta-analysis of Djabri et al (2002).…”
Section: Stage 2: Estimation Of the Parameterssupporting
confidence: 76%
“…This is precisely the density of blood-derived PMN necessary to exert optimal bactericidal (Staph. aureus) activity in milk, as reported by Herbelin et al (1997), but higher than 6 × 10 5 cells/ mL, as reported by Postle et al (1978). It is also close to the SCC value (1,151,000 cells/mL) reported in the meta-analysis of Djabri et al (2002).…”
Section: Stage 2: Estimation Of the Parameterssupporting
confidence: 76%
“…Therefore, when multicomponent antigens were used in mastitis vaccine, combined adjuvants may be more effective and useful than one adjuvant in immune response. This results of the study aggrees with earlier studies [5,10,13,14,16].…”
Section: Discussionsupporting
confidence: 88%
“…The crude alpha-toxin was confirmed by 12% (w/v) sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western blot [11]. The hemolytic assay is a serial two-fold dilution of 50% hemolysis end point assay described by Herbelin et al [10] and Harshman et al [9].…”
Section: Methodsmentioning
confidence: 99%
“…The investigators concluded that under circumstances of chronic inflammation, in which the growth of bacteria and the consequent elaboration of ␣-toxin are controlled, toxigenicity may not contribute significantly to virulence. Interestingly, ␣-toxin itself triggers the recruitment of neutrophils to a site of infection (16). The importance of neutrophils in controlling S. aureus growth and toxin production is also evident from studies in which depletion of neutrophils resulted in a conversion of a subclinical infection with toxigenic staphylococci into acute mastitis (29).…”
Section: Discussionmentioning
confidence: 99%